(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: The root canal along with its complex anatomic difficulties poses a challenge to the endodontist while approaching to remove the old obturating material held within its confines during re-treatment procedures. An ideal root canal solvent hastens this process of dissolution of Gutta Percha without causing procedural errors in the process. Aim & Objective: To compare and evaluate the solubilizing efficacy of Orange Oil, Eugenol and Tween 80 on Gutta Percha. Materials and Methods: A total of seventy-five conventional gutta percha cones having ISO size 30 and 4% taper were selected for the study. The Gutta Percha cones were then divided into three groups at random: Group I: Orange Oil; Group II: Eugenol; Group III: Tween 80. The cones were pre weighted using an electronic weighing balance and noted as the Pre immersion weight (M1). Following this they were immersed for 15min in clear glass vials containing 2ml of the solvents in each of them. The cones were then post weighted and noted (M2). The difference in weights of the gutta percha cones was evaluated. Results: Orange oil showed the highest efficacy in solubilizing Gutta Percha. This was followed by Tween 80 which was a novel solvent used for dissolution. Eugenol proved to be least efficacious in dissolving. Conclusion: Orange oil showed superior solubilizing efficacy when compared to Tween 80 and Eugenol.prone to develop CTS. Larger research is needed to understand how physical exercise causes CTS. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.167-171